Kaempferol Attenuates Cardiac Hypertrophy via Regulation of ASK1/MAPK Signaling Pathway and Oxidative Stress - Feng, Hong; Cao, Jianlei; Zhang, Guangyu; Wang, Yanggan (Planta Medica, 2017)
Kaempferol has been demonstrated to provide benefits for the treatment of atherosclerosis, coronary heart disease, hyperlipidemia, and diabetes through its antioxidant and anti-inflammatory properties. However, its role in cardiac hypertrophy remains to be elucidated. The aim of our study was to investigate the effects of kaempferol on cardiac hypertrophy and the underlying mechanism. Mice subjected to aorta banding were treated with or without kaempferol (100 mg/kg/d, p. o.) for 6 weeks. Echocardiography was performed to evaluate cardiac function. Mice hearts were collected for pathological observation and molecular mechanism investigation. H9c2 cardiomyocytes were stimulated with or without phenylephrine for in vitro study. Kaempferol significantly attenuated cardiac hypertrophy induced by aorta banding as evidenced by decreased cardiomyocyte areas and interstitial fibrosis, accompanied with improved cardiac functions and decreased apoptosis. The ASK1/MAPK signaling pathways (JNK1/2 and p38) were markedly activated in the aorta banding mouse heart but inhibited by kaempferol treatment. In in vitro experiments, kaempferol also inhibited the activity of ASK1/JNK1/2/p38 signaling pathway and the enlargement of H9c2 cardiomyocytes. Furthermore, our study revealed that kaempferol could protect the mouse heart and H9c2 cells from pathological oxidative stress. Our investigation indicated that treatment with kaempferol protects against cardiac hypertrophy, and its cardioprotection may be partially explained by the inhibition of the ASK1/MAPK signaling pathway and the regulation of oxidative stress.
Keywords: kaempferol; cardiac hypertrophy; MAPK; ASK1; oxidative stress